Oligomeric S100A4 Is Associated With Monocyte Innate Immune Memory and Bypass of Tolerance to Subsequent Stimulation With Lipopolysaccharides - Neidhart, Michel; Pajak, Agnieszka; Laskari, Katerina; Riksen, Niels P.; Joosten, Leo A. B.; Netea, Mihai G.; Lutgens, Esther; Stroes, Eric S. G.; Ciurea, Adrian; Distler, Oliver; Grigorian, Mariam; Karouzakis, Emmanuel (Frontiers in Immunology, 2019)
Objectives. Most DAMPs in inflammatory diseases are TLR2- and TLR4-ligands and according to the current concept, repeated stimuli would result in tolerance. Aims of the study were to verify this assumption, to investigate whether epigenetic effectors are involved and to explore the situation in rheumatoid arthritis (RA). Methods. A trained immunity (TI) and tolerance protocol was established using peripheral blood monocytes from heathy donors,beta-glucan and lipopolysaccharide (LPS). The training or tolerance capacities of RA-relevant DAMPs were tested. Results. Beta-glucan-, oS100A4-, HMBG1- and HSP90-pretreated monocytes showed increased IL-6 responses to LPS re-stimulation. Beta-glucan, oS100A and tenascin C induced training of monocytes to release more TNF. In comparison to beta-glucan, most DAMPs tested induced less TI, with exception of oS100A4. Monocytes exposed to oS100A4 showed increased IL-1beta, IL-6 and TNFalpha in response to LPS, in spite that both stimulate TLR4. RNASEq upon beta-glucan or oS100A4 revealed similar changes in chemokines/cytokines and epigenetic effectors; 17 epigenetic effectors correlated with chemokine/cytokine gene expression; PRDM8 was associated with more chemokine and cytokine transcripts. Knockdown of PRDM8 abolished TI induced by oS100A4. In RA, plasma S100A4 correlated with increased CSF2, and increased PRDM8 transcription in RA monocytes was associated with increased plasma CCL5 and IL-6, as well as therapy-resistance. Conclusion. Bypass of tolerance by DAMPs might be a phenomenon as important as TI, since it could explain how chronic inflammation can be maintained in spite of an environment with multiple TLR2/TLR4-ligands. In RA monocytes, a PRDM8-dependent TI mechanism could be responsible for sustained chemokine/cytokines levels.